PEMANFAATAN APLIKASI VIDEO CALL WHATSAPP PADA TPQ MIFTAUL ULUM GEDONGKUNING YOGYAKARTA - naning ma'rifatul faiqoh (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2021)
Abstract: Research on the use of the whatsaap video call application in the Al-Quran education park Miftahul Ulum Gedongkuning Yogyakarta using qualitative descriptive research methods, conducting interviews with 6 informants, observation, and literature study. The research objectives: 1) to determine the constraints of whatsaap video calls in the activities of the TPQ Miftahul Ulum Yogyakarta students 2) to determine the impact of whatsaap video calls in the activities of the TPQ Miftahul Ulum Yogyakarta students. The results of the study were 1) Obstacles to whatsaap video calls in the activity of reciting TPQ Miftahul Ulum Gedongkuning students from the results of interviews by several informants that the lack of time to recite the recitation and when reciting took place sometimes the signal was interrupted which caused the sound to falter and even stop so that a signal was available or educator / ustadz / ah turn off the camera feature so that the signal is focused only on the sound. 2) Two-way communication and lots of support makes this activity run well, and really helps the santri guardians in the development of the Koran for children. This activity can also introduce children in a positive way, that the whatsaap video call media can be used in the realm of learning and the guardians of the students feel that the child is more focused on the Koran, after reading the child is reminded of inappropriate / wrong readings and the child feels responsible because at the end of the session children are reminded to read the previous / next page and will be checked for tomorrow's meeting.